Conceptualizing Quality in Participatory Health Research: A Phenomenographic Inquiry - Jane Springett; Kayla Atkey; Krystyna Kongats; Rosslynn Zulla; Emma Wilkins (Forum: Qualitative Social Research, 2016)
Participatory approaches to research are gaining popularity in health and wellness disciplines because of their potential to bridge gaps between research and practice and promote health equity. A number of guidelines have been developed to help research-practitioners gauge the quality of participatory health research (PHR). In light of the increasing popularization of this approach in the field of public health, there is a need to check in with current practitioners to see if their practices are still reflective of past guidelines. The aim of this study was to understand how research-practitioners currently conceptualize the quality of participatory health research in particular. Using phenomenographic inquiry, we interviewed 13 researchers who described their experience of PHR. We identified 15 categories of description and visually represented the relationship between the categories using an outcome space. Our findings suggest that conceptualizations of what is considered high quality PHR have remained consistent. This reliability bodes well for the development of quality criteria for participatory health research. We discuss implications for scaling up this study to compare quality criteria beyond a North American context.